Using Collaborative Coalition Processes to Advance Community Health, Well-Being, and Equity: A Multiple–Case Study Analysis From a National Community Transformation Initiative. (October 2019) - Reid, Amy; Abraczinskas, Michelle; Scott, Victoria; Stanzler, Morgen; Parry, Gareth; Scaccia, Jonathan; Wandersman, Abe; Ramaswamy, Rohit
Spreading Community Accelerators Through Learning and Evaluation (SCALE) was a Robert Wood Johnson Foundation–funded initiative from 2015 to 2017 to build capability of 24 community coalitions to advance health, well-being, and equity. The SCALE theory of change had three components: develop leadership capability, build relationships within and between communities, and create an intercommunity system to spread promising ideas. The theory was operationalized through training academies, coaching, and peer-to-peer learning that explicitly addressed equity and systems change. In this article, we describe how SCALE facilitated community transformation related to Collaborating for Equity and Justice Principles 1, 3, 4, and 6. We conducted a multiple–case study approach with two community coalitions including site visits, interviews, and observation to illuminate underlying mechanisms of change by exploring how and why change occurs. Skid Row Women worked with women experiencing homelessness in Los Angeles to address diabetes and food systems. Healthy Livable Communities of Cattaraugus County used a portfolio of projects in order to create system changes to improve population health and increase access to services for people with disabilities in rural New York State. Through our analysis, we describe how two coalitions used SCALE tools for collaborative coalition processes such as aim setting, relationship building, and shared decision making with community residents. Our findings suggest that advancing Collaborating for Equity and Justice principles requires self-reflection and courage; new ways of being in relationship; learning from failure; productive conflict to explicitly address power, racism, and other forms of oppression; and methods to test systems improvement ideas.